Systematic review of child maltreatment screening tools used by different occupational groups: a study protocol - Denise Colley; Ertan Mayatepek; Freia De Bock; Lena Rasch; Jenny Seidler; Britta Gahr; Lisa Küppers; Philipp Rollbühler (BMJ Open)
Background Child maltreatment (CM) encompasses physical, emotional or sexual abuse, physical or emotional/psychological neglect or intimate partner (or domestic) violence and is associated with adverse cognitive, behavioural, physical and social outcomes that often continue shaping adulthood. The early and valid detection of CM is essential to initiate treatment and intervention as well as to avoid continued violence against the child. Various occupational groups, such as healthcare providers, teachers, social workers, psychotherapists and others, encounter maltreated children in their professional settings. Systematic reviews on instruments to assess suspected CM often report on retrospective measurement via caregiver’s or child’s self-report and are frequently limited to the health system as a setting. The purpose of this Preferred Reporting Items for Systematic Reviews and Meta-Analyses-compliant systematic review is to synthesise the evidence on psychometric properties of instruments to assess suspected CM at the presentation to a broad range of different occupational groups who work with children inside and outside the healthcare system.Method A systematic search will be performed in Scopus, PsycInfo, Medline and Web of Science with no limit on the earliest publication until January 2022. Eligibility criteria include studies that investigate psychometric properties of instruments to assess suspected CM in children and adolescents under 18 years by a professional proxy. After the independent screening of studies by two reviewers, quality assessment and data extraction will be performed using an adaptation of the COnsensus‐based Standards for the selection of health Measurement INstruments Risk of Bias checklist, Strengthening the Reporting of Observational Studies in Epidemiology: Explanation and Elaboration report and Downs and Black checklist for measuring study quality. Screening, quality assessment and data extraction will be done using Covidence. The results will be presented in narrative form and, if adequate, a meta-analysis will be performed.Discussion This review aims to give an overview of the psychometric properties of different instruments designed to screen suspected CM by professional proxies. The results will be of interest to different occupational groups who need information about methodological quality and characteristics of instruments to make decisions about the best-suited tool for a specific purpose. Furthermore, the results of this review will support the development of novel instruments and might improve the existing ones.Ethics and dissemination Ethics approval will not be required. The results of this systematic review will be submitted for publication in a peer-reviewed journal.PROSPERO registration number CRD42022297997.